Brine shrimp lethality assay with selected medicinal plants extracts - Suneka, S.; Manoranjan, T. (University of Jaffna, 2021)
Brine Shrimp Lethality Assay (BSLA) is a preliminary and important screening tool for cytotoxicity. This assay monitors toxic substances in plant extract and other based solvents. The toxic substance kills laboratory cultured larvae (nauplii). Artemia salina (nauplii), the first larval stage of many crustaceans, having an unsegmented body and a single eye. It is about 22 mm long. Organic extracts of the three terrestrial medicinal plants were investigated for the biological activity against BSLA with the help of Artemia salina. Those selected plant extracts were also tested for phytochemical analysis. The goal of the study is to evaluate the cytotoxicity of each plant extract and compare the activity among them by using BSLA test data. For the analysis, dried plant leaves and aerial parts were grounded into fine powder. About 500 grams of powder was extracted by cyclohexane, dichloromethane (DCM) and methanol respectively. The extract were filtered and concentrated in rotatory evaporator and each crude weight were recorded. According to the BSLA test of these plant extracts, the DCM extracts of Tephrosia purpurea (Sarphonka (E), Kavila (T)), Andrographis paniculata (Kings of bitter (E), Nilavembu (T)) and Oldenlandia umbellata (Chay root (E), Chaaya ver (T)) showed high activity than other solvents extracts. The LC50 (fifty percentage lethality concentration) value of dichloromethane extracts of T. purpurea was shown high value as 104.712 ppm, while A. paniculata and O. umbellate were shown 125.89 ppm and 223.872 ppm respectively. This result indicates the variety of active compound/s responsible for activity in the extracts especially in the DCM extracts.
Keywords: BSLA; Artemia salina; Tephrosia purpurea; Andrographis paniculata; Oldenlandia umbellata